Arthroscopic anatomical double-bundle anterior cruciate ligament reconstruction for asian patient using a bone-patellar tendon-bone and gracilis tendon composite autograft: a technical note - Tajima Takuya; Chosa Etsuo; Yamamoto Keitaro; Yamaguchi Nami (BMC, 2012)
Abstract Background Recent years have seen anterior cruciate ligament (ACL) reconstruction being performed in a broad range of patients, regardless of age, sex and occupation, thanks to great advances in surgical techniques, surgical instruments and basic research. In cases of ACL reconstruction, bone-patellar tendon-bone (BTB) graft or hamstring graft are frequency used. However, potential complications associated with tunnel enlargement due to soft tissue graft such as hamstring were reported. On the other hand, an altered rotational axis resulting in significantly greater translation of the lateral compartment in the single bundle compared with double bundle ACL reconstruction was reported. Method and procedure A reconstruction procedure was modified for the ACL using a double bundle that is the combination of BTB and gracilis tendon composite autograft. Two tibial and two femoral bone tunnels are used to reconstruct two bundles of ACL; an anteromedial bundle (AMB) and a posterolateral bundle (PLB). The femoral bone tunnels are created just posterior to the resident's ridge. The tibial bone tunnels are created at the center of AM and PL tibial attachment, respectively. BTB is fixed in the AM tunnels produced on the anatomical points of tibia and femur. The gracilis graft is fixed in an anatomical PL tunnel produced. The mean width of BTB is 7 mm, since10 mm graft is sometimes not suitable for patients, especially small Asian people and females. For these patients, 10 mm graft is bigger than one third of patella tendon width. Conclusion The devised surgical procedure based on a combination of BTB and gracilis autograft is suitable reconstruction method for patients who have small or medium width of patellar tendon such as Asian people and females. This technique is also applicable to revision surgery.